Low platinum-nickel iron nitrogen composite self-supporting electrode and application thereof
A low-platinum-nickel-iron-nitrogen composite self-supporting electrode was prepared by an anodic oxidation coupled electrodeposition method, which solved the problems of high cost of platinum group metals and general performance of nickel-iron-based electrocatalysts. It achieved a highly efficient bifunctional catalysis with low platinum loading, with excellent hydrogen evolution and oxygen evolution performance, and is suitable for the field of water electrolysis.
Patent Information
- Application Number
- CN202511834830.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-08
- Publication Date
- 2026-02-03
AI Technical Summary
In existing technologies, the high cost and scarcity of platinum group metals in the field of electrocatalysis limit their large-scale application, and simple nickel-iron-based electrocatalysts generally have poor hydrogen evolution performance, making it difficult to achieve efficient bifunctional catalysis in electrochemical water splitting.
An electrochemical method of anodic oxidation coupled electrodeposition was adopted, in which platinum and nickel sheets were electrochemically reacted in hydrochloric acid aqueous solution containing ferric chloride and melamine to prepare a low platinum-nickel-iron-nitrogen composite self-supporting electrode. Combined with the electrochemical co-deposition of nickel, iron and nitrogen elements, bifunctional catalytic activity was achieved with low platinum loading.
The prepared low-platinum-nickel-iron-nitrogen composite self-supporting electrode exhibits excellent hydrogen evolution and oxygen evolution performance in water electrolysis, reducing the amount of precious metals used, improving catalytic activity and stability, simplifying electrode processing, reducing costs, and showing broad prospects for industrial application.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochemical materials technology, and in particular to a low platinum-nickel-iron-nitrogen composite self-supporting electrode and its application. Background Technology
[0002] Platinum group metals (PGMs) possess significant advantages and wide applications in electrocatalysis. Due to their unique d-electron orbital structures, PGMs (such as platinum, iridium, and ruthenium) provide optimal adsorption and desorption kinetic balance for reactants, significantly reducing the activation energy of electrocatalytic reactions and thus being widely used in cathode catalysis processes. For example, platinum (Pt) exhibits extremely high activity in the hydrogen evolution reaction (HER), efficiently adsorbing and dissociating hydrogen atoms. PGM-based intermetallic compounds, due to their excellent catalytic performance and tunable electronic structures, have become a research hotspot in the field of catalytic materials in recent years, and are widely used in green energy and sustainable chemical industries. Despite the numerous advantages of PGMs in electrocatalysis, their high cost and scarcity limit their large-scale application. Therefore, current research focuses on developing efficient composite catalysts, reducing the amount of precious metals used, and exploring non-precious metal alternatives. How to achieve high electrocatalytic activity and stability while reducing platinum loading is a key problem that urgently needs to be solved.
[0003] In water splitting, using different catalyst electrodes as the cathode and anode significantly increases material and process manufacturing costs. There is an urgent need to construct a non-precious metal material with excellent catalytic performance and economic characteristics for bifunctional catalytic water splitting, exhibiting both good hydrogen evolution and oxygen evolution performance. Nickel-iron-based electrocatalysts are considered alternatives to precious metal catalysts for oxygen evolution reactions in alkaline solutions due to their excellent catalytic activity. However, the generally poor hydrogen evolution performance of simple nickel-iron-based electrocatalysts limits their application in electrochemical water splitting. Combining the advantages of precious metal platinum with transition metal nickel-iron to prepare a low-platinum-nickel-iron bifunctional composite catalyst with excellent hydrogen evolution and oxygen evolution performance has broad application prospects in water electrolysis. Furthermore, current research indicates that nitrogen doping can modify the electronic structure of the catalyst surface, increasing its adsorption energy for hydrogen or water molecules and enhancing the intrinsic catalytic activity of transition metals. Therefore, doping with nitrogen during the preparation of low-platinum-nickel-iron bifunctional composite catalysts is expected to improve their catalytic activity. Summary of the Invention
[0004] This invention aims to provide a low-platinum-nickel-iron-nitrogen composite self-supporting electrode based on electrochemical preparation and its application. This invention utilizes an anodic oxidation coupled with electrodeposition as an electrochemical method to prepare a low-platinum-nickel-iron-nitrogen composite self-supporting electrode, which offers advantages such as low cost, high catalytic activity, and bifunctional catalysis in water electrolysis applications.
[0005] The technical solution of the present invention is as follows: This invention provides a low-platinum-nickel-iron-nitrogen composite self-supporting electrode, which is prepared by the following method: using a platinum sheet as the anode and a nickel sheet as the cathode, with a distance of 2-3 cm between the anode and cathode, and using an aqueous hydrochloric acid solution containing ferric chloride and melamine as the electrolyte, an electrochemical anodizing and cathode electrodeposition coupling reaction is carried out for 1-5 h under constant voltage of 10-30 V and temperature of 40-60 ℃ (preferably 50 ℃), and the low-platinum-nickel-iron-nitrogen composite self-supporting electrode is obtained by cathode deposition.
[0006] Furthermore, in the hydrochloric acid aqueous solution containing ferric chloride and melamine, the concentration of ferric chloride is 0.604~3.625 mmol / L, the concentration of melamine is 0.785~4.71 mmol / L, the concentration of hydrochloric acid is 0.6~2.4 mol / L, and water is used as the solvent.
[0007] Furthermore, the platinum and nickel sheets undergo the following pretreatment before use: the platinum and nickel sheets are ultrasonically cleaned for 30 minutes with a mixed solution of acetone, ethanol and deionized water in a volume ratio of 3:2:5 to remove surface grease, then rinsed with deionized water and dried for later use.
[0008] Furthermore, the thickness of the platinum sheet is 0.05~1 mm, and the thickness of the nickel sheet is 0.1~1 mm. (The platinum sheet and the nickel sheet are respectively metallic platinum and metallic nickel with a purity greater than 99%).
[0009] Furthermore, in the hydrochloric acid aqueous solution containing ferric chloride and melamine, the concentration of ferric chloride is 0.604~2.417 mmol / L (more preferably 0.604~1.813 mmol / L), the concentration of melamine is 0.785~3.14 mmol / L (more preferably 0.785~2.355), and the concentration of hydrochloric acid is 0.6~1.8 mol / L.
[0010] Furthermore, the constant voltage of the electrochemical anodic oxidation and cathodic electrodeposition coupling reaction is 15~25 V (more preferably 17.5 V~22.5 V), and the reaction time is 1~3 h.
[0011] Furthermore, the coupling reaction temperature of the electrochemical anodic oxidation and cathodic electrodeposition is 50 °C.
[0012] Furthermore, the distance between the anode and the cathode is 2 cm.
[0013] This invention also provides an application of a low-platinum-nickel-iron-nitrogen composite self-supporting electrode as a bifunctional catalyst in water electrolysis for hydrogen and oxygen production.
[0014] Furthermore, the application is as follows: in the electrolysis of water to produce hydrogen, a three-electrode system is used, with the aforementioned low-platinum-nickel-iron-nitrogen composite self-supporting electrode as the working electrode, a graphite electrode as the auxiliary electrode, and an Hg / HgO electrode as the reference electrode. The electrolyte is 1 mol·L⁻¹. ¹ KOH solution is used for water electrolysis to produce hydrogen by applying a cathode potential; in the water electrolysis to produce oxygen, a three-electrode system is used, with the aforementioned low-platinum-nickel-iron-nitrogen composite self-supporting electrode as the working electrode, a graphite electrode as the auxiliary electrode, and a Hg / HgO electrode as the reference electrode. The electrolyte is 1 mol·L⁻¹. ¹ KOH solution, using the same electrode system and electrolyte as described above, is used to electrolyze water and generate oxygen by applying an anodic potential.
[0015] The low platinum-nickel-iron-nitrogen composite self-supporting electrode described in this invention can catalyze both hydrogen evolution reaction and oxygen evolution reaction in a dual-function manner, and can be used in the field of water electrolysis.
[0016] The technical principles of this invention include: This invention utilizes the trace electrochemical dissolution characteristics of platinum metal at the anode in an acidic electrolyte, while combining the dynamic equilibrium of chemical dissolution and electrodeposition of nickel at the cathode, and the electrodeposition of iron ions and nitrogen elements in the electrolyte at the cathode, to achieve the electrochemical co-deposition of all four elements at the cathode. This method, while controlling the amount of platinum deposited, incorporates nickel, iron, and nitrogen elements, increasing the bifunctionality of the self-supporting catalyst and enhancing its catalytic activity.
[0017] The beneficial effects of this invention are as follows: This invention utilizes metallic nickel as a substrate and employs an anodic oxidation coupled with electrodeposition to fabricate a low-platinum-nickel-iron-nitrogen composite self-supporting electrode in a hydrochloric acid aqueous solution containing ferric chloride and melamine. This low-platinum-nickel-iron-nitrogen composite self-supporting electrode is a bifunctional self-supporting electrode exhibiting both hydrogen evolution catalytic activity and oxygen evolution catalytic activity. Its preparation process is simple, requires minimal reaction equipment, has a low platinum loading, and offers high economic benefits. By controlling the electrolyte composition, reaction temperature, reaction voltage, and reaction time, self-supporting electrodes with different structures and compositions can be obtained on the metal surface, thereby improving the electrocatalytic activity and stability of the composite self-supporting electrode. It has broad application prospects in industrial applications.
[0018] The low platinum-nickel-iron-nitrogen composite self-supporting electrode prepared by this invention, compared with traditional electrode materials, does not require additional binders and conductive agents, effectively promotes the exposure of active sites, and simplifies electrode processing. It can not only effectively promote electron transfer, but also prevent catalyst agglomeration or detachment, and has broad application prospects in industrial applications. Attached Figure Description
[0019] Figure 1Comparison of the low platinum-nickel-iron-nitrogen composite self-supporting electrode prepared in Example 1 (left) and the unreacted pure nickel sheet used (right).
[0020] Figure 2 Scanning electron microscope (SEM) image of the low platinum-nickel-iron-nitrogen composite self-supporting electrode prepared in Example 1.
[0021] Figure 3 Mapping image of the surface of the low platinum-nickel-iron-nitrogen composite self-supporting electrode prepared in Example 1.
[0022] Figure 4 X-ray diffraction (XRD) pattern of the low platinum-nickel-iron-nitrogen composite self-supporting electrode prepared in Example 1.
[0023] Figure 5 : Hydrogen evolution performance of the low platinum-nickel-iron-nitrogen composite self-supporting electrode prepared in Example 1 in an alkaline system.
[0024] Figure 6 : Oxygen evolution performance of the low platinum-nickel-iron-nitrogen composite self-supporting electrode prepared in Example 1 in an alkaline system.
[0025] Figure 7 Scanning electron microscope (SEM) image of the low platinum-nickel-iron-nitrogen composite self-supporting electrode prepared in Example 2.
[0026] Figure 8 Scanning electron microscope (SEM) image of the low platinum-nickel-iron-nitrogen composite self-supporting electrode prepared in Example 3.
[0027] Figure 9 Scanning electron microscope (SEM) image of the low platinum-nickel-iron-nitrogen composite self-supporting electrode prepared in Example 4.
[0028] Figure 10 Scanning electron microscope (SEM) image of the low platinum-nickel-iron-nitrogen composite self-supporting electrode prepared in Example 5.
[0029] Figure 11 Scanning electron microscope (SEM) image of the low platinum-nickel-iron-nitrogen composite self-supporting electrode prepared in Example 6.
[0030] Figure 12 Scanning electron microscope (SEM) image of the low platinum-nickel-iron-nitrogen composite self-supporting electrode prepared in Example 7.
[0031] Figure 13 Scanning electron microscope (SEM) image of the low platinum-nickel-iron-nitrogen composite self-supporting electrode prepared in Example 8.
[0032] Figure 14Scanning electron microscope (SEM) image of the low-load platinum-nickel-iron-nitrogen composite self-supporting electrode prepared in Example 9.
[0033] Figure 15 Scanning electron microscope (SEM) image of the low platinum-nickel-iron-nitrogen composite self-supporting electrode prepared in Example 10.
[0034] Figure 16 Scanning electron microscope (SEM) image of the low platinum-nickel-iron-nitrogen composite self-supporting electrode prepared in Example 11. Detailed Implementation
[0035] To make the technical means, creative features, objectives and effects of this invention easy to understand, the invention will be specifically described below in conjunction with embodiments and accompanying drawings.
[0036] Example 1
[0037] Cut a 0.085 mm thick platinum sheet into 1×2 cm pieces. 2 The nickel sheet, with a thickness of 0.2 mm, was cut into 0.5 × 2 cm pieces. 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution (200 mL) of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and dried to obtain degreased and de-oiled metal platinum and nickel electrodes.
[0038] An electrolyte was prepared by adding 5 mg of anhydrous ferric chloride (98% purity), 10 mg of melamine (99% purity), and 5 mL of hydrochloric acid (36-38% purity) to 45 mL of deionized water. The concentrations of ferric chloride, melamine, and hydrochloric acid in the electrolyte were 0.604 mmol / L, 1.57 mmol / L, and 1.2 mol / L, respectively.
[0039] A platinum sheet was used as the anode and a nickel sheet as the cathode. The electrodes were placed in an electrolyte with a spacing of 2 cm, the electrolyte temperature was controlled at 50 °C, the reaction voltage was 22.5 V, and the reaction time was 2 h. After the reaction was completed, the cathode sample was removed, the sample surface was washed with deionized water and dried to obtain a low platinum-nickel-iron-nitrogen composite self-supporting electrode.
[0040] The prepared low platinum-nickel-iron-nitrogen composite self-supporting electrode is as follows: Figure 1 As shown. Its SEM image is as follows. Figure 2 As shown, numerous spherical particles are formed on the electrode surface and are evenly distributed. Its mapping diagram is as follows. Figure 3 As shown, nickel, platinum, iron, and nitrogen elements are relatively evenly distributed, with platinum distributed on the surfaces of nickel and iron. Its XRD pattern is shown below. Figure 4 As shown, it contains Ni, Pt2Ni2 and Fe6N2.21 Characteristic peaks were observed, and a low-platinum-nickel-iron-nitrogen composite self-supporting electrode was successfully fabricated.
[0041] Its hydrogen evolution performance in alkaline systems is as follows: Figure 5 As shown, at 100 mA·cm -2 At the specified current density, the overpotential of the low-platinum-nickel-iron-nitrogen composite self-supporting electrode was only 90.4 mV, while the overpotential of the commercial 20% Pt / C catalyst at the same current density was 175.4 mV. This indicates that the low-platinum-nickel-iron-nitrogen composite self-supporting electrode exhibits superior hydrogen evolution performance compared to the commercial Pt / C catalyst. Electrocatalytic hydrogen evolution performance testing was conducted on the Shanghai Chenhua electrochemical workstation (CHI760E). A three-electrode system was used, with the prepared low-platinum-nickel-iron-nitrogen composite self-supporting electrode as the working electrode, a graphite electrode as the auxiliary electrode, and an Hg / HgO electrode as the reference electrode. The electrolyte was 1 mol·L⁻¹. -1 KOH solution.
[0042] Its oxygen evolution performance in alkaline systems is as follows: Figure 6 As shown, at 100 mA·cm -2 At the specified current density, the overpotential of the low-platinum-nickel-iron-nitrogen composite self-supporting electrode was only 299.6 mV, while the overpotential of commercial RuO2 at the same current density was 378.6 mV, indicating that the low-platinum-nickel-iron-nitrogen composite self-supporting electrode has superior oxygen evolution performance compared to the commercial RuO2 catalyst. The electrocatalytic oxygen evolution performance was tested on the Shanghai Chenhua electrochemical workstation (CHI760E). A three-electrode system was used, with the prepared low-platinum-nickel-iron-nitrogen composite self-supporting electrode as the working electrode, a graphite electrode as the auxiliary electrode, and an Hg / HgO electrode as the reference electrode. The electrolyte was 1 mol·L⁻¹. -1 KOH solution.
[0043] Example 2
[0044] Cut a 0.085 mm thick platinum sheet into 1×2 cm pieces. 2 The nickel sheet, with a thickness of 0.2 mm, was cut into 0.5 × 2 cm pieces. 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution (200 mL) of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and dried to obtain degreased and de-oiled metal platinum and nickel electrodes.
[0045] An electrolyte was prepared by adding 5 mg of anhydrous ferric chloride (98% purity), 10 mg of melamine (99% purity), and 5 mL of hydrochloric acid (36-38% purity) to 45 mL of deionized water. The concentrations of ferric chloride, melamine, and hydrochloric acid in the electrolyte were 0.604 mmol / L, 1.57 mmol / L, and 1.2 mol / L, respectively.
[0046] A platinum sheet was used as the anode and a nickel sheet as the cathode, both immersed in an electrolyte solution with an electrode spacing of 2 cm. The electrolyte temperature was controlled at 50 °C, the reaction voltage at 17.5 V, and the reaction time at 2 h. After the reaction, the cathode sample was removed, its surface was washed with deionized water, and then dried to obtain a low-platinum-nickel-iron-nitrogen composite self-supporting electrode. Its SEM image is shown below. Figure 7 As shown, because the reaction voltage is lower than that in Example 1, the electrodeposition reaction is insufficient, and only a small amount of deposits are produced.
[0047] Example 3
[0048] Cut a 0.085 mm thick platinum sheet into 1×2 cm pieces. 2 The nickel sheet, with a thickness of 0.2 mm, was cut into 0.5 × 2 cm pieces. 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution (200 mL) of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and dried to obtain degreased and de-oiled metal platinum and nickel electrodes.
[0049] An electrolyte was prepared by adding 5 mg of anhydrous ferric chloride (98% purity), 10 mg of melamine (99% purity), and 5 mL of hydrochloric acid (36-38% purity) to 45 mL of deionized water. The concentrations of ferric chloride, melamine, and hydrochloric acid in the electrolyte were 0.604 mmol / L, 1.57 mmol / L, and 1.2 mol / L, respectively.
[0050] A platinum sheet was used as the anode and a nickel sheet as the cathode, both immersed in an electrolyte solution with an electrode spacing of 2 cm. The electrolyte temperature was controlled at 50 °C, the reaction voltage at 25 V, and the reaction time at 2 h. After the reaction, the cathode sample was removed, its surface was washed with deionized water, and then dried to obtain a low-platinum-nickel-iron-nitrogen composite self-supporting electrode. Its SEM image is shown below. Figure 8 As shown, due to the higher reaction voltage than in Example 1, the amount of deposited products increased, and excessive deposition led to sediment agglomeration and increased size.
[0051] Example 4
[0052] Cut a 0.085 mm thick platinum sheet into 1×2 cm pieces. 2 The nickel sheet, with a thickness of 0.2 mm, was cut into 0.5 × 2 cm pieces. 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution (200 mL) of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and dried to obtain degreased and de-oiled metal platinum and nickel electrodes.
[0053] An electrolyte was prepared by adding 5 mg of anhydrous ferric chloride (98% purity), 5 mg of melamine (99% purity), and 5 mL of hydrochloric acid (36-38% purity) to 45 mL of deionized water. The concentrations of ferric chloride, melamine, and hydrochloric acid in the electrolyte were 0.604 mmol / L, 0.785 mmol / L, and 1.2 mol / L, respectively.
[0054] A platinum sheet was used as the anode and a nickel sheet as the cathode, both immersed in an electrolyte solution with an electrode spacing of 2 cm. The electrolyte temperature was controlled at 50 °C, the reaction voltage at 22.5 V, and the reaction time at 2 h. After the reaction, the cathode sample was removed, its surface was washed with deionized water, and then dried to obtain a low-platinum-nickel-iron-nitrogen composite self-supporting electrode. Its SEM image is shown below. Figure 9 As shown, the amount of melamine added is less than that in Example 1, resulting in less surface deposits, no further product deposition on the surface deposits, and smaller pores between the deposits.
[0055] Example 5
[0056] Cut a 0.085 mm thick platinum sheet into 1×2 cm pieces. 2 The nickel sheet, with a thickness of 0.2 mm, was cut into 0.5 × 2 cm pieces. 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution (200 mL) of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and dried to obtain degreased and de-oiled metal platinum and nickel electrodes.
[0057] An electrolyte was prepared by adding 5 mg of anhydrous ferric chloride (98% purity), 15 mg of melamine (99% purity), and 5 mL of hydrochloric acid (36-38% purity) to 45 mL of deionized water. The concentrations of ferric chloride, melamine, and hydrochloric acid in the electrolyte were 0.604 mmol / L, 2.355 mmol / L, and 1.2 mol / L, respectively.
[0058] A platinum sheet was used as the anode and a nickel sheet as the cathode, both immersed in an electrolyte solution with an electrode spacing of 2 cm. The electrolyte temperature was controlled at 50 °C, the reaction voltage at 22.5 V, and the reaction time at 2 h. After the reaction, the cathode sample was removed, its surface was washed with deionized water, and then dried to obtain a low-platinum-nickel-iron-nitrogen composite self-supporting electrode. Its SEM image is shown below. Figure 10 As shown, the amount of melamine added was more than that in Example 1, resulting in increased surface deposits and larger gaps between the deposits. However, agglomeration occurred, forming larger clusters, which was not as uniformly distributed as in Example 1.
[0059] Example 6
[0060] Cut a 0.085 mm thick platinum sheet into 1×2 cm pieces. 2 The nickel sheet, with a thickness of 0.2 mm, was cut into 0.5 × 2 cm pieces. 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution (200 mL) of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and dried to obtain degreased and de-oiled metal platinum and nickel electrodes.
[0061] An electrolyte was prepared by adding 10 mg of anhydrous ferric chloride (98% purity), 10 mg of melamine (99% purity), and 5 mL of hydrochloric acid (36-38% purity) to 45 mL of deionized water. The concentrations of ferric chloride, melamine, and hydrochloric acid in the electrolyte were 1.208 mmol / L, 1.57 mmol / L, and 1.2 mol / L, respectively.
[0062] A platinum sheet was used as the anode and a nickel sheet as the cathode, both immersed in an electrolyte solution with an electrode spacing of 2 cm. The electrolyte temperature was controlled at 50 °C, the reaction voltage at 22.5 V, and the reaction time at 2 h. After the reaction, the cathode sample was removed, its surface was washed with deionized water, and then dried to obtain a low-platinum-nickel-iron-nitrogen composite self-supporting electrode. Its SEM image is shown below. Figure 11 As shown, due to the increased amount of ferric chloride added compared to Example 1, the sediment particle size increased, but there were still abundant voids between the particles.
[0063] Example 7
[0064] Cut a 0.085 mm thick platinum sheet into 1×2 cm pieces. 2 The nickel sheet, with a thickness of 0.2 mm, was cut into 0.5 × 2 cm pieces. 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution (200 mL) of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and dried to obtain degreased and de-oiled metal platinum and nickel electrodes.
[0065] An electrolyte was prepared by adding 15 mg of anhydrous ferric chloride (98% purity), 10 mg of melamine (99% purity), and 5 mL of hydrochloric acid (36-38% purity) to 45 mL of deionized water. The concentrations of ferric chloride, melamine, and hydrochloric acid in the electrolyte were 1.813 mmol / L, 1.57 mmol / L, and 1.2 mol / L, respectively.
[0066] A platinum sheet was used as the anode and a nickel sheet as the cathode, both immersed in an electrolyte solution with an electrode spacing of 2 cm. The electrolyte temperature was controlled at 50 °C, the reaction voltage at 22.5 V, and the reaction time at 2 h. After the reaction, the cathode sample was removed, its surface was washed with deionized water, and then dried to obtain a low-platinum-nickel-iron-nitrogen composite self-supporting electrode. Its SEM image is shown below. Figure 12 As shown, since the amount of ferric chloride added is further increased compared to the amount of ferric chloride added in Examples 1 and 2, the amount of sediment increases accordingly, filling the gaps between particles and resulting in excessively dense sediment particles.
[0067] Example 8
[0068] Cut a 0.085 mm thick platinum sheet into 1×2 cm pieces. 2 The nickel sheet, with a thickness of 0.2 mm, was cut into 0.5 × 2 cm pieces. 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution (200 mL) of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and dried to obtain degreased and de-oiled metal platinum and nickel electrodes.
[0069] An electrolyte was prepared by adding 5 mg of anhydrous ferric chloride (98% purity), 10 mg of melamine (99% purity), and 2.5 mL of hydrochloric acid (36-38% purity) to 47.5 mL of deionized water. The concentrations of ferric chloride, melamine, and hydrochloric acid in the electrolyte were 0.604 mmol / L, 1.57 mmol / L, and 0.6 mol / L, respectively.
[0070] A platinum sheet was used as the anode and a nickel sheet as the cathode, both immersed in an electrolyte solution with an electrode spacing of 2 cm. The electrolyte temperature was controlled at 50 °C, the reaction voltage at 22.5 V, and the reaction time at 2 h. After the reaction, the cathode sample was removed, its surface was washed with deionized water, and then dried to obtain a low-platinum-nickel-iron-nitrogen composite self-supporting electrode. Its SEM image is shown below. Figure 13 As shown, the hydrochloric acid concentration was reduced compared to that in Example 1, resulting in a smaller amount of sediment, varying sediment size, and uneven distribution.
[0071] Example 9
[0072] Cut a 0.085 mm thick platinum sheet into 1×2 cm pieces. 2 The nickel sheet, with a thickness of 0.2 mm, was cut into 0.5 × 2 cm pieces. 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution (200 mL) of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and dried to obtain degreased and de-oiled metal platinum and nickel electrodes.
[0073] An electrolyte was prepared by adding 5 mg of anhydrous ferric chloride (98% purity), 10 mg of melamine (99% purity), and 7.5 mL of hydrochloric acid (36-38% purity) to 42.5 mL of deionized water. The concentrations of ferric chloride, melamine, and hydrochloric acid in the electrolyte were 0.604 mmol / L, 1.57 mmol / L, and 1.8 mol / L, respectively.
[0074] A platinum sheet was used as the anode and a nickel sheet as the cathode, both immersed in an electrolyte solution with an electrode spacing of 2 cm. The electrolyte temperature was controlled at 50 °C, the reaction voltage at 22.5 V, and the reaction time at 2 h. After the reaction, the cathode sample was removed, its surface was washed with deionized water, and then dried to obtain a low-platinum-nickel-iron-nitrogen composite self-supporting electrode. Its SEM image is shown below. Figure 14 As shown, the hydrochloric acid concentration was higher than that in Example 1, resulting in increased sedimentation, severe sediment agglomeration, and increased sediment size.
[0075] Example 10
[0076] Cut a 0.085 mm thick platinum sheet into 1×2 cm pieces. 2 The nickel sheet, with a thickness of 0.2 mm, was cut into 0.5 × 2 cm pieces. 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution (200 mL) of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and dried to obtain degreased and de-oiled metal platinum and nickel electrodes.
[0077] An electrolyte was prepared by adding 5 mg of anhydrous ferric chloride (98% purity), 10 mg of melamine (99% purity), and 5 mL of hydrochloric acid (36-38% purity) to 45 mL of deionized water. The concentrations of ferric chloride, melamine, and hydrochloric acid in the electrolyte were 0.604 mmol / L, 1.57 mmol / L, and 1.2 mol / L, respectively.
[0078] A platinum sheet was used as the anode and a nickel sheet as the cathode, both immersed in an electrolyte solution with an electrode spacing of 2 cm. The electrolyte temperature was controlled at 50 °C, the reaction voltage at 22.5 V, and the reaction time at 1 h. After the reaction, the cathode sample was removed, its surface was washed with deionized water, and then dried to obtain a low-platinum-nickel-iron-nitrogen composite self-supporting electrode. Its SEM image is shown below. Figure 15 As shown, although the reaction time was reduced compared to Example 1, the deposits were still relatively uniformly distributed. However, due to the reduced deposition time, fewer particles were redeposited on the deposits, resulting in smaller gaps between the outermost deposit particles on the electrode surface.
[0079] Example 11
[0080] Cut a 0.085 mm thick platinum sheet into 1×2 cm pieces. 2 The nickel sheet, with a thickness of 0.2 mm, was cut into 0.5 × 2 cm pieces. 2 The electrodes were ultrasonically cleaned for 30 min in a mixed solution (200 mL) of acetone, ethanol and deionized water in a volume ratio of 3:2:5, rinsed with deionized water and dried to obtain degreased and de-oiled metal platinum and nickel electrodes.
[0081] An electrolyte was prepared by adding 5 mg of anhydrous ferric chloride (98% purity), 10 mg of melamine (99% purity), and 5 mL of hydrochloric acid (36-38% purity) to 45 mL of deionized water. The concentrations of ferric chloride, melamine, and hydrochloric acid in the electrolyte were 0.604 mmol / L, 1.57 mmol / L, and 1.2 mol / L, respectively.
[0082] A platinum sheet was used as the anode and a nickel sheet as the cathode, both immersed in an electrolyte solution with an electrode spacing of 2 cm. The electrolyte temperature was controlled at 50 °C, the reaction voltage at 22.5 V, and the reaction time at 3 h. After the reaction, the cathode sample was removed, its surface was washed with deionized water, and then dried to obtain a low-platinum-nickel-iron-nitrogen composite self-supporting electrode. Its SEM image is shown below. Figure 16 As shown, the reaction time was longer than that of Example 1, resulting in excessive deposited products and obvious agglomeration.
[0083] The above embodiments are preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention.
[0084] Comparative Example 1
[0085] According to the method of Chinese patent CN114289032B: First, the glassy carbon electrode was pretreated: It was polished to a mirror finish on chamois leather using a 0.05 μm alumina polishing slurry in a figure-eight pattern. After polishing, it was ultrasonically cleaned in ethanol to remove residual polishing powder. 4 mg of commercial Pt / C catalyst powder was accurately weighed and dissolved in 0.9 mL of isopropanol, with 0.1 mL of Nafion solution added as a binder and proton conductor. The mixture was ultrasonically treated for 1 hour to form a homogeneous and stable suspension. Then, 4 μL of catalytic ink was carefully pipetted onto the center surface of the pretreated glassy carbon electrode, allowing the droplet to spread naturally due to surface tension. The electrode was then placed at room temperature to allow the solvent to evaporate slowly and uniformly, resulting in a glassy carbon electrode loaded with 20% Pt / C electrocatalyst. Replacing the 4 mg of commercial Pt / C catalyst powder with 4 mg of RuO2 powder, while continuing the same steps, yielded a glassy carbon electrode loaded with commercial RuO2 electrocatalyst.
[0086] The comparison figure shows the hydrogen evolution performance of a glassy carbon electrode with a 20% Pt / C electrocatalyst and a low-platinum-nickel-iron-nitrogen composite self-supporting electrode prepared in the comparative example. Figure 5 As shown in the figure; a comparison of the oxygen evolution performance of the glassy carbon electrode with RuO2 electrocatalyst prepared in the comparative example and the low platinum-nickel-iron-nitrogen composite self-supporting electrode is shown in the figure. Figure 6 As shown, the low-platinum-nickel-iron-nitrogen composite self-supporting electrode prepared in Example 1 exhibits superior hydrogen evolution performance compared to commercial Pt / C catalysts, and superior oxygen evolution performance compared to commercial RuO2 electrocatalysts. The electrocatalytic hydrogen evolution performance tests of the 20% Pt / C electrocatalyst and the electrocatalytic oxygen evolution performance tests of the commercial RuO2 electrocatalyst were conducted on the Shanghai Chenhua electrochemical workstation (CHI760E). A three-electrode system was used, with the prepared glassy carbon electrode supported on 20% Pt / C electrocatalyst and the glassy carbon electrode supported on RuO2 electrocatalyst as working electrodes, a graphite electrode as the auxiliary electrode, and an Hg / HgO electrode as the reference electrode. The electrolyte was 1 mol·L⁻¹. -1 KOH solution was electrolyzed to produce hydrogen by applying a cathode potential and to produce oxygen by applying an anode potential.
[0087] The comparison shows that this method, through anodizing coupled with electrodeposition, prepares a low-platinum-nickel-iron-nitrogen composite self-supporting electrode. This method is simple in its preparation process and requires less sophisticated reaction equipment. Both the platinum and nickel sources in this method are derived from metal electrodes, and the amount of platinum used is minimal. The platinum sheets can be reused, resulting in lower cost and higher economic efficiency. The catalyst prepared by this method is a self-supporting electrocatalyst. Compared to the catalyst powder application process in the comparative example, it avoids the use of binders and other additives. This binder-free, integrated structure facilitates the exposure of the catalyst's active sites, effectively promoting electron transfer and reducing catalyst agglomeration or detachment, thus showing broad application prospects in the energy field.
Claims
1. A low-platinum-nickel-iron-nitrogen composite self-supporting electrode, characterized in that, The low-platinum-nickel-iron-nitrogen composite self-supporting electrode is prepared by the following method: using a platinum sheet as the anode and a nickel sheet as the cathode, with a distance of 2-3 cm between the anode and cathode, and using an aqueous hydrochloric acid solution containing ferric chloride and melamine as the electrolyte, electrochemical anodizing and cathode electrodeposition coupling reaction is carried out for 1-5 h under constant voltage of 10-30 V and temperature of 40-60 ℃, and the low-platinum-nickel-iron-nitrogen composite self-supporting electrode is obtained by cathode deposition.
2. The low platinum-nickel-iron-nitrogen composite self-supporting electrode as described in claim 1, characterized in that, In the hydrochloric acid aqueous solution containing ferric chloride and melamine, the concentration of ferric chloride is 0.604~3.625 mmol / L, the concentration of melamine is 0.785~4.71 mmol / L, the concentration of hydrochloric acid is 0.6~2.4 mol / L, and water is used as the solvent.
3. The low platinum-nickel-iron-nitrogen composite self-supporting electrode as described in claim 1, characterized in that, Before use, the platinum and nickel sheets undergo the following pretreatment: they are ultrasonically cleaned for 30 minutes with a mixed solution of acetone, ethanol and deionized water in a volume ratio of 3:2:5 to remove surface grease, then rinsed with deionized water and dried for later use.
4. The low platinum-nickel-iron-nitrogen composite self-supporting electrode as described in claim 1, characterized in that, The thickness of the platinum sheet is 0.05~1 mm, and the thickness of the nickel sheet is 0.1~1 mm.
5. The low platinum-nickel-iron-nitrogen composite self-supporting electrode as described in claim 2, characterized in that, In the hydrochloric acid aqueous solution containing ferric chloride and melamine, the concentration of ferric chloride is 0.604 ~ 2.417 mmol / L, the concentration of melamine is 0.785 ~ 3.14 mmol / L, and the concentration of hydrochloric acid is 0.6 ~ 1.8 mol / L.
6. The low platinum-nickel-iron-nitrogen composite self-supporting electrode as described in claim 1, characterized in that, The constant voltage for the coupled electrochemical anodic oxidation and cathodic electrodeposition reaction is 15~25 V, and the reaction time is 1~3 h.
7. The low platinum-nickel-iron-nitrogen composite self-supporting electrode as described in claim 1, characterized in that, The coupling reaction temperature of the electrochemical anodic oxidation and cathodic electrodeposition is 50 °C.
8. The low platinum-nickel-iron-nitrogen composite self-supporting electrode as described in claim 1, characterized in that, The distance between the anode and the cathode is 2 cm.
9. The application of the low platinum-nickel-iron-nitrogen composite self-supporting electrode as described in claim 1 as a bifunctional catalyst in water electrolysis for hydrogen and oxygen production.
10. The application as described in claim 9, characterized in that, The application is as follows: In the electrolysis of water for hydrogen evolution, a three-electrode system is used, with the aforementioned low-platinum-nickel-iron-nitrogen composite self-supporting electrode as the working electrode, a graphite electrode as the auxiliary electrode, and an Hg / HgO electrode as the reference electrode. The electrolyte is 1 mol·L⁻¹. ¹ KOH solution is used for water electrolysis to produce hydrogen by applying a cathode potential; in the water electrolysis to produce oxygen, a three-electrode system is used, with the aforementioned low-platinum-nickel-iron-nitrogen composite self-supporting electrode as the working electrode, a graphite electrode as the auxiliary electrode, and a Hg / HgO electrode as the reference electrode. The electrolyte is 1 mol·L⁻¹. ¹ KOH solution, using the same electrode system and electrolyte as described above, is used to electrolyze water and generate oxygen by applying an anodic potential.
Citation Information
Patent Citations
Preparation method and application of tungsten oxide-supported platinum-iron nano-alloy catalyst
CN114289032B
